Identification of Cystathionine β‐Synthase Inhibitors Using a Hydrogen Sulfide Selective Probe1. Issue 17 (19th March 2013) - Thorson, Megan K.; Majtan, Tomas; Kraus, Jan P.; Barrios, Amy M.
<x xml:space="preserve">Abstract</x> Buzzing with activity: A hydrogen sulfide selective fluorogenic probe, 7‐azido‐4‐methylcoumarin (AzMC), serves as a highly sensitive assay for cystathionine β‐synthase activity, and is suitable for the high‐throughput discovery of novel enzyme inhibitors.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>